AIECE General Report: Part 2, Spring 2023 - Andrej Drygalla; Axel Lindner; Birgit Schultz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2023)
The Halle Institute for Economic Research (IWH) is a member of AIECE (Association d'Instituts Europeens de Conjoncture Economique/Association of European Conjuncture Institutes), an association of independent European institutes involved in surveying economic conditions and developments, and in short-term macroeconomic forecasting. The main objective of the Association is to stimulate the exchanges between its members with a view to improve their insight into international economic developments. This ranges from the exchange of statistical or institutional information to discussions on economic policy Guidelines to common research activities. The AIECE organises between its members an exchange of view, of information and of literature on international economic developments, in particular in Europe. The Association provides the framework for joint activities of its members in areas of common interest. Its structure allows its members to develop common views on the future cyclical development. In order to meet these objectives the Association has half-yearly plenary meetings, centred around a general report on the European conjuncture prepared in turn by one of the members in cooperation with the other member institutes, but also with discussions of the working group reports and of special surveys prepared by member institutes. In Spring 2023, the report was written by the Halle Institute for Economic Research (IWH).
Keywords: 330